2008
DOI: 10.1167/iovs.07-0868
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire Analysis and New Pathogenic Epitopes of IRBP in C57BL/6 (H-2b) and B10.RIII (H-2r) Mice

Abstract: Several new pathogenic peptides of IRBP were identified in C57BL/6 and B10.RIII mice. Differences in epitope recognition between WT and IRBP KO mice were observed in C57BL/6 mice, but not in B10.RIII mice, suggesting more extensive culling of the repertoire in C57BL/6 mice by endogenously expressed IRBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…Together these data pointed to the presence of a pathogenic epitope or epitopes within subunit 3. As the severity of disease induced by this subunit was greater than that previously reported for the non-immunodominant peptide 651-670, 12 this raised the possibility that additional epitopes might be present.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Together these data pointed to the presence of a pathogenic epitope or epitopes within subunit 3. As the severity of disease induced by this subunit was greater than that previously reported for the non-immunodominant peptide 651-670, 12 this raised the possibility that additional epitopes might be present.…”
Section: Resultsmentioning
confidence: 78%
“…Human RBP-3 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Peptide (GPTHLFQPSLVLDMAKV LLD) and chicken ovalbumin (OVA) (ISQAVHAAHAEIN EAGR) were synthesized by Sigma-Aldrich (Poole, UK).…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This EAU model differs in immunological, clinical, and pathological characteristics from the traditional IRBP-CFA model, in which the disease is shorter and less severe. The fundus lesions are punctates and there are more neutrophils than monocytes (48) . This autoimmune uveitis model demonstrates that the same antigen may induce different forms of uveitis, depending on how they are presented to the immune system, and may help to explain the heterogeneity of human uveitis (48) .…”
Section: New Models Of Experimental Autoimmune Uveitismentioning
confidence: 99%
“…Approximately 84% of the bovine and human IRBP present identical sequence of amino acids (44,45) . Many studies using EAU models induced by IRBP have aimed the identification of the exact immunogenic epitopes (46)(47)(48) and interactions with the MHC molecules. Specific IRBP epitopes ha ve already been recognized as uveitogenic in susceptible mice strains: Peptide 1-20 for C57BL/6, 161-180 for B10.RIII, and 201-216 for B10.A (49) , and recent studies revealed several additional uveitogenic epitopes of human IRBP molecule that elicit EAU in mice (48) .…”
Section: Interphotoreceptor Retinoid-binding Proteinmentioning
confidence: 99%